FROM MARKETING TO NEUROMARKETING: EMOTION AT THE SERVICE OF THE COMPANY - Restrepo Restrepo, Santiago (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
Since the 1990s, technologies have been developed that reveal in detail the functioning of the human brain in all its daily actions. One of them is consumption, making purchasing decisions. The process that takes place in the making of elections in relation to neuromarketing is deeply embedded in the brain circuits of consumers in order to better understand the motivations and processes that precede decision making in the human being. Currently in the business world it is not enough to analyze what customers say, or to observe how they behave, it is also necessary to investigate the neurocognitive mechanisms involved in these actions. It is more important to discover “what you think” the person to recognize “what he says he thinks”.